2022
DOI: 10.3390/rel13050393
|View full text |Cite
|
Sign up to set email alerts
|

Unchaste Celibates: Clergy Sexual Misconduct against Adults—Expressions, Definitions, and Harms

Abstract: There is an ignored, misunderstood, and complex reality within the broader clergy sexual abuse scandal within the Roman Catholic Church (RCC)—that of clergy sexual misconduct against adults (CSMAA). Estimates and calculations of numbers of victims/survivors over the last half-century reach into the early millions. Furthermore, evidence reveals that CSMAA does produce many serious personal, relational, and practical harms. This article presents and discusses the many expressions of such harms. However, even wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, the consequences may be seen mainly in people confronting the clergy's misconduct in forms of betrayed trust and psychological and physical harm. [31][32][33][34] It can be concluded that the religious world shared common terms in describing misconduct; the common attributes were extortion, misuse of authority, abusive behaviors, and breaking the vows. The antecedents were a lack of attachment to religiosity and dysfunctional families, negligence, and misuse of authority and power.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the consequences may be seen mainly in people confronting the clergy's misconduct in forms of betrayed trust and psychological and physical harm. [31][32][33][34] It can be concluded that the religious world shared common terms in describing misconduct; the common attributes were extortion, misuse of authority, abusive behaviors, and breaking the vows. The antecedents were a lack of attachment to religiosity and dysfunctional families, negligence, and misuse of authority and power.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Betrayed trust and psychological and physical harm were the expected consequences of misconduct. [30][31][32][33][34]…”
Section: Literature Reviewmentioning
confidence: 99%